Outcome of 46 children with refractory leukemia treated with unrelated donor hematopoietic stem cell transplantation - Chen, Jing (Zhonghua er ke za zhi = Chinese journal of pediatrics, 2010)
OBJECTIVE: To evaluate the efficacy of matched unrelated donor hematopoietic stem cell transplantation (UDT) and influencing factors in children with refractory leukemia